Heat transfer augmentation in concentric elliptic annular by ethylene glycol based nanofluids - Dawood H.K.; Mohammed H.A.; Sidik N.A.C.; Munisamy K.M.; Alawi O.A. (Elsevier Ltd, 2023)
Aluminum; Copper oxides; Ethylene; Ethylene glycol; Finite volume method; Heat convection; Heat flux; Heat transfer; Heat transfer coefficients; Mixed convection; Nanoparticles; Nusselt number; Polyols; Reynolds number; Volume fraction; Zinc oxide; Annulus; Governing equations; Heat transfer augmentation; Heat Transfer enhancement; Nanofluids; Nanoparticle diameter; Nanoparticle volume fractions; Numerical investigations; Nanofluidics